LEITURA E PRODUÇÃO ESCRITA DO GÊNERO RELATÓRIO PARA DESENVOLVIMENTO DE HABILIDADES - Gregório, Nadirce Barros dos Santos (Intercâmbio, 2010)
The purpose of this paper is to discuss the proposal of introducing undergraduates to the reading and writing of reports. It is believed that introducting activities to develop these abilities can help the students to face communication demands.